Skeletal development of hallucal tarsometatarsal joint curvature and angulation in extant apes and modern humans. Issue 88 (November 2015) - Gill, Corey M.; Bredella, Miriam A.; DeSilva, Jeremy M.
Abstract: The medial cuneiform, namely the curvature and angulation of its distal facet with metatarsal 1, is crucial as a stabilizer in bipedal locomotion and an axis upon which the great toe medially deviates during arboreal locomotion in extant apes. Previous work has shown that facet curvature and angulation in adult dry-bone specimens can distinguish African apes from Homo, and can even distinguish among species of Gorilla . This study provides the first ontogenetic assessment of medial cuneiform curvature and angulation in juvenile (n = 68) and adult specimens (n = 102) using computed tomography in humans and extant ape specimens, including Pongo . Our data find that modern human juveniles initially have a convex and slightly medially oriented osseous surface of the developing medial cuneiform distal facet that flattens and becomes more distally oriented with age. The same pattern (though of a different magnitude) occurs developmentally in the chimpanzee medial cuneiform, but not in Gorilla or Pongo, whose medial cuneiform facet angulation remains unchanged ontogenetically. These data suggest that the medial cuneiform ossifies in a distinguishable pattern between Pongo, Gorilla, Pan, and Homo, which may in part be due to subtle differences in the loading environment at the hallucal tarsometatarsal joint—a finding that has important implications for interpreting fossil medial cuneiforms.